Social History of Outsider Migration and Politics of Essentialisms in Amrabad Tiger Reserve, Telangana, India - Sahithi Sanaka; Siddhartha Krishnan (Rural Landscapes: Society Environment History, 2025)
Chenchus, the native tribes (Adivasis/indigenous) of the Amrabad plateau in the Nallamala hill ranges of the Eastern Ghats in Telangana, India, are portrayed and academically studied as ‘primitive’ or ‘naïve foragers’. Their symbiotic association with forests, life in isolation in an economy based on subsistence, and their requirement for protection from outsiders and market mechanisms are central to how they are governed. Studies analysing multiple ways of governing nature-society relations argue that similar global representations of indigenous communities serve to assemble an ‘ethno-environmental fix’ that seemingly attends to the concerns of protecting the vulnerable population and fragile biodiverse environments from market mechanisms. This study explored the region’s social history to unravel the historicity of the popular portrayals, neglected realities, and the purposes such portrayals serve, and it argues that the popular representations of Chenchus are de-historisized, essentialist portrayals. They blanket the frontier dynamics, historic interactions of Chenchus with the outside world, migratory pasts and socio-economic characteristics of settlers from different castes and the agrarian transformation in the landscape. It further argues that the implementation of the Forest Rights Act (an ethno-environmental fix), in such contexts, with its limitations and outcomes, serves the protection regime in multiple ways. They aid the protection regime in gaining dominance and control over the land that is historically contested and retained by the radicals and settlers, in creating potentially inviolate or people-less-protected areas and diverting the contestations away from its oppressive rule towards inter-community differences while gaining legitimacy without excessive reliance on violent measures.